Base‐Pairing Behavior of a Carbocyclic Janus‐AT Nucleoside Analogue Capable of Recognizing A and T within a DNA Duplex. Issue 16 (23rd September 2013) - Largy, Eric; Liu, Wenbo; Hasan, Abid; Perrin, David M.
Abstract Janus‐type nucleosides are heterocycles with two faces, each of which is designed to complement the H‐bonding interactions of natural nucleosides comprising a canonical Watson–Crick base pair. By intercepting all of the hydrogen bonds contained within the base pair, oligomeric Janus nucleosides are expected to achieve sequence‐specific DNA recognition through the formation of J‐loops that will be more stable than D‐loops, which simply replaces one base‐pair with another. Herein, we report the synthesis of a novel Janus‐AT nucleoside analogue, JAT, affixed on a carbocyclic analogue of deoxyribose that was converted to the corresponding phosphoramidite. A single JAT was successfully incorporated into a DNA strand by solid phase for targeting both A and T bases, and characterized through biophysical and computational methods. Experimental UV‐melting and circular dichroism data demonstrated that within the context of a standard duplex, JAT associates preferentially with T over A, and much more poorly with C and G. Density functional theory calculations confirm that the JAT structure is well suited to associate only with A and T thereby highlighting the importance of the electronic structure in terms of H‐bonding. Finally, molecular dynamics simulations validated the observation that JAT can substitute more effectively as an A‐analogue than as a T‐analogue without substantial distortion of the B‐helix. Overall, this new Janus nucleotide is a promising tool for the targeting of A–T base pairs in DNA, and will lead to the development of oligo‐Janus‐nucleotide strands for sequence‐specific DNA recognition.